Pengaruh Fear of Missing Out, Brand Image dan Influencer Marketing Terhadap Keputusan Pembelian Produk Skincare Glad2glow - Amira, Amira; Fietroh, Muhammad Nur (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of Fear of Missing Out (FOMO), Brand Image, and Influencer Marketing on the purchasing decisions of Glad2glow skincare products among students of the Faculty of Economics and Business at the University of Technology Sumbawa. The rapid growth of the skincare industry is driven by lifestyle changes among the younger generation and the increasing role of social media as a primary tool in digital marketing. As part of the digital native generation, students are highly responsive to beauty trends influenced by social anxiety (FOMO), brand perception, and influencer recommendations. Using a quantitative survey method with multiple linear regression analysis on a sample of 100 respondents, the results show that all three variables, FOMO, Brand Image, and Influencer Marketing, have a positive and significant impact on purchasing decisions, with Influencer Marketing being the most dominant factor. These findings highlight the importance for skincare businesses and digital marketers to develop strategies that harness the power of FOMO, establish a strong brand image, and effectively utilize influencers to enhance customer loyalty and sales conversions within the student market segment, while also contributing to the theoretical development of digital marketing literature in the era of digital transformation.